LINGUISTICS SEEKING SUBJECT - L. K. Zhanalina; L. V. Fot (Вестник Кемеровского государственного университета, 2016)
The paper provides a brief overview of the evolution of one of the main lines of inquiry into how linguistics perceives its subject. Its oscillations vary from abstract language modelling to attempts to comprehend its reality, supported by a transition from purely linguistic approaches to interdisciplinary ones. A broad conception of language, characteristic in the contemporary language studies, is demonstrated by development of an anthropocentric paradigm which is a foundation for integrative ideology. The latter strives to holistic representation of language and proliferates via multiplication of intra-linguistic integrative models as well as via interdisciplinary descriptions of language. Both have to combat limitations of scientific knowledge through their merger on the basis of integrative approaches. Among these, a high potential for language reality comprehension is demonstrated by K. Wilber, his AQAL model of conscience is universal and applicable to subjects from different fields of study, including that of language.